2015
DOI: 10.1021/acs.est.5b03521
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Shift Drives Antibiotic Resistance Promotion during Drinking Water Chlorination

Abstract: For comprehensive insights into the effects of chlorination, a widely used disinfection technology, on bacterial community and antibiotic resistome in drinking water, this study applied high-throughput sequencing and metagenomic approaches to investigate the changing patterns of antibiotic resistance genes (ARGs) and bacterial community in a drinking water treatment and distribution system. At genus level, chlorination could effectively remove Methylophilus, Methylotenera, Limnobacter, and Polynucleobacter, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
143
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(164 citation statements)
references
References 57 publications
19
143
2
Order By: Relevance
“…Therefore, as bacterial diversity changes across soils, so do their associated ARGs, resulting in resistome that may respond to anthropogenic modulations that even do not possess obvious antibiotic-related properties (such as chemical fertilizer). The similar results were found in a recent study on drinking water system indicating that the major driver of antibiotic resistome alternation was bacterial community shift rather than MGEs reproduction or transference (Jia et al, 2015). In addition, our previous work also found that MGEs contributed only 2.6% of the resistome variation during sewage sludge composting .…”
Section: Linkages Between Bacterial Community and Antibiotic Resistomesupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, as bacterial diversity changes across soils, so do their associated ARGs, resulting in resistome that may respond to anthropogenic modulations that even do not possess obvious antibiotic-related properties (such as chemical fertilizer). The similar results were found in a recent study on drinking water system indicating that the major driver of antibiotic resistome alternation was bacterial community shift rather than MGEs reproduction or transference (Jia et al, 2015). In addition, our previous work also found that MGEs contributed only 2.6% of the resistome variation during sewage sludge composting .…”
Section: Linkages Between Bacterial Community and Antibiotic Resistomesupporting
confidence: 89%
“…An important finding from this work is that bacterial community shifts play a dominant role in shaping the antibiotic resistome in soil. Although, HGT via MGEs is often regarded as the underlying mechanism responsible for the resistome formation and spread under different ecological niches (Jia et al, 2015). In this study MGEs explained only 4.1% variation of ARGs.…”
Section: Linkages Between Bacterial Community and Antibiotic Resistomementioning
confidence: 49%
“…Recent studies have demonstrated that variations in microbial community structure and mobile genetic elements (MGEs) were significantly correlated with ARG profiles in soil, sludge, and drinking water (Forsberg et al 2014;Jia et al 2015;Su et al 2015). However, riverine microbiota are exposed to a number of environmental factors including toxins, nutrients, hypoxia, and habitat alterations.…”
Section: Responsible Editor: Robert Duranmentioning
confidence: 99%
“…Armstrong et al [28] noted that the proportion of multiple antibiotic-resistant phenotypes increased during chlorination for Gram-positive cocci and Gram-negative, non-fermentative rods. In addition, Jia et al [29] revealed that a total of 151 antibiotic-resistance genes were detectable in the drinking water, and chlorination evidently increase their total relative abundance, while reducing their diversity in the opportunistic bacteria.…”
Section: Inactivation Ratio Of Vre and Detection Of Vana In Secondarymentioning
confidence: 99%